In Vitro Antiplasmodial Activity and Cytotoxicity of Active Subfractions of Harmsiopanax aculeatus Leaves - Rachel Turalely; Mahardika Agus Wijayanti; Triana Hertiani; Musthofa Mustofa (Indonesian Journal of Pharmacy, 2020)
Harmsiopanax aculeatus leaves, a medicinal plant with locally named kapur, have been used traditionally to treat malaria in Maluku, Indonesia. However, the scientific information of this plant is still limited. In our previous study, the methanol extract of this plant leaves have been proven to possess in vitro antiplasmodial activity. This study was conducted to evaluate in vitro antiplasmodial activity and cytotoxicity of  subfractions of the plant leaves. Fractionation was performed using a column chromatography with Sephadex LH-20 as the  stationary phase and methanol as the mobile phase. The subfractions obtained were then tested for in vitro antiplasmodial activity on a chloroquine-resistant FCR3 strain of Plasmodium falciparum using a visual method. Cytotoxicity was evaluated by using MTT assay. The in vitro antiplasmodial activity and cytotoxicity were expressed as IC50, calculated using probit analysis with SPSS 16 for windows. The results showed that the four subfractions tested have a high antiplasmodial activity with IC50 values of 0.09; 0.18; 0.01; and 0.77 µg.mL-1, respectively. In addition, these subfractions had IC50 values of >400 µg.mL-1 against Vero cells indicating that they were non-toxic. In conclusion, the subfractions of H. aculeatus leaves are very active and selective against P. falciparum. Further study will be conducted to isolate the active compounds.